1972
DOI: 10.1104/pp.49.3.430
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Development of Increased Ion Absorption in Corn Root Tissue

Abstract: Washing excised or intact primary roots of corn (Zea mays L., WF9 X M14) in aerated distilled water or dilute salt solutions for 2 hours induced doubling of the rate of accumulation of various nutrient ions and solutes. This response to washing depended upon aerobic metabolism, but involved no increase in aerobic respiration. Excision of root tissue was not required as the effect could be obtained with intact root systems. Increased phosphate absorption followed afer a lag period of 30 to 40 minutes and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
73
1
3

Year Published

1972
1972
1990
1990

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 25 publications
9
73
1
3
Order By: Relevance
“…In the present study, washing corn root segments in aerated K-phosphate and CaCl2 solutions increased the rate of K+ (wRb) uptake by 5-fold with little or no lag and the rate leveled off after 4 h. In contrast, washing increased phosphate uptake by only 2-to 3-fold during the same 4-h period with an initial lag of 30 to 40 min. These results agree well with previous studies on the stimulation of ion uptake by washing (5,13,16,19 …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, washing corn root segments in aerated K-phosphate and CaCl2 solutions increased the rate of K+ (wRb) uptake by 5-fold with little or no lag and the rate leveled off after 4 h. In contrast, washing increased phosphate uptake by only 2-to 3-fold during the same 4-h period with an initial lag of 30 to 40 min. These results agree well with previous studies on the stimulation of ion uptake by washing (5,13,16,19 …”
Section: Resultssupporting
confidence: 83%
“…Previous studies with excised corn root segments have shown that washing immediately increased K+ uptake activity (5,19) and membrane potential (15) with uptake increasing by 3-to 7-fold and the membrane potential increasing to a maximum of 25 mv within 4 h. In contrast to K+, Pi uptake (13,16) increases only 2-3-fold after a 30-min lag period. Based on these washing response data and the study of the effect of dithioerythritol on membrane potential, resistance, and proton fluxes (17), Hanson and Lin (7,17) suggested that active salt transport and its regulation arise from the functioning of a proton-extruding, cation-carrying ATPase in the membrane, balanced by H+/cation and OH-/anion antiporters.…”
mentioning
confidence: 96%
“…16), there is a gradual recovery of these physiological attributes; rapid recovery is produced by fusicoccin. Injury also initiates a rapid net K+ efflux from the tissue, which after 45 to 60 min reverses to a net influx (9,13). Initial leakage of K+ from wounded or shocked plant tissues is a commonly observed phenomenon (15,16).…”
Section: ) With Washing (Or 'Adaptive Aging'mentioning
confidence: 99%
“…Seedlings were grown on toweling as described in the accompanying paper (25). Inductive washing was by immersion of sections in well aerated 0.2 mm CaCl2 solution.…”
mentioning
confidence: 99%